Mental health-related stigma discrimination and prejudices among Greek healthcare professionals - Porfyri, Georgia-Nektaria; Athanasiadou, Maria; Siokas, Vasileios; Giannoglou, Sofia; Skarpari, Sofia; Kikis, Michail; Myroforidou, Artemis; Anoixa, Maria; Zerakis, Nikolaos; Bonti, Eleni; Konsta, Anastasia; Diakogiannis, Ioannis; et al. (Frontiers in Psychiatry, 2022)
Introduction Research shows that mental health-related stigma, stereotypes, and prejudices have a negative impact on the patients themselves as well as on their families and social entourage. Healthcare professionals, whose expertise and professional ethos are historically acknowledged by public opinion, are expected to play a major role in combating discrimination against psychiatric patients. In this study, we aimed to assess the attitudes of Greek healthcare professionals toward mental illness and people suffering from it. Materials and methods It is a non-interventional, analytic study, in which 479 health workers from a tertiary hospital in Thessaloniki, Greece, participated. Every single hospital service –except the personnel of the Psychiatric Clinic– was included in our study: from the cleaning service to the administrative staff and the auxiliary staff such as stretcher carriers, food and nutrition services’ staff, and social workers, the nursing staff, and finally the attending physicians, taking into consideration that the psychiatric patient, from the moment he/she enters the hospital, consecutively gets in contact with every work grade of the healthcare establishment. Participants’ attitudes concerning mental illness have been evaluated using the Opinions about Mental Illness Scale (OMI), the Social Distance Scale (SDS), and the Level of Contact Report (LCR-12). Results Despite the high level of familiarity [as evaluated with LCR-12; mean score (μ): 8.82 ± 1.73], the employees displayed a rather poor willingness to interact with psychiatric patients (as measured with SDS; μ:11.68 ± 4.28), and endorsed significant prejudice toward individuals with mental disorders (assessed using OMI subscales; Social Discrimination μ: 22.99 ± 12.08, Social Restriction μ: 17.45 ± 9.07, Social Care μ: 21.04 ± 4.12, Social Integration μ: 16.38 ± 4.68, Etiology μ: 9.80 ± 4.95). Age and education stood out as the main determinants of participants’ attitudes, with younger and highly educated participants to have shown a relatively refined profile. Conclusion These results are not significantly improved compared to those of previous decades in Greek healthcare professionals and call for critical reflection and targeted stigma-reduction efforts.